2017
DOI: 10.1093/rheumatology/kex053
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary behaviour in rheumatoid arthritis: definition, measurement and implications for health

Abstract: Rheumatoid Arthritis (RA) is a chronic autoimmune disease characterised by high gradeinflammation, and associated with elevated cardiovascular risk, rheumatoid-cachexia and functional impairment. Sedentary behaviour is linked to heightened inflammation, and is highly pervasive in RA -likely as a result of compromised physical function and persistent fatigue. This high sedentarity may exacerbate the inflammatory process in RA, and hold relevance for disease-related outcomes. The aim of this narrative review is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 77 publications
(105 reference statements)
0
53
1
Order By: Relevance
“…Rheumatoid arthritis (RA) is associated with an excess risk for cardiovascular disease (CVD), attributable partly to traditional cardiovascular risk factors (1)(2)(3) and partly to the systemic inflammation present in RA (2,4). An insufficient level of physical activity has also been presented as a contributory factor to the CVD morbidity in RA (5)(6)(7)(8). Physical activity, defined as 'any bodily movement produced by skeletal muscles that results in energy expenditure' (9), is strongly protective against CVD morbidity and mortality in the general population, and has the potential of affecting cardiovascular risk factors (10,11) as well as inflammation (12).…”
mentioning
confidence: 99%
“…Rheumatoid arthritis (RA) is associated with an excess risk for cardiovascular disease (CVD), attributable partly to traditional cardiovascular risk factors (1)(2)(3) and partly to the systemic inflammation present in RA (2,4). An insufficient level of physical activity has also been presented as a contributory factor to the CVD morbidity in RA (5)(6)(7)(8). Physical activity, defined as 'any bodily movement produced by skeletal muscles that results in energy expenditure' (9), is strongly protective against CVD morbidity and mortality in the general population, and has the potential of affecting cardiovascular risk factors (10,11) as well as inflammation (12).…”
mentioning
confidence: 99%
“…It has been reported that people living with RA typically spend long periods of time sedentary, 3,29,30 and recent accelerometry studies suggest people with this condition can spend up to 9 waking hours sedentary per day. 31,32 On the basis of emerging evidence for the association between SB and inflammation, Fenton and Kitas 29 hypothesised that high levels of SB in RA may exacerbate already elevated systemic inflammation in these patients, and contribute to the progression of RA outcomes. Akin to this proposition, Fenton et al 31 summarised results of non-RA studies, demonstrating the adverse links between SB with inflammation and chronic diseases with an inflammatory component (e.g., CVD, type 2 diabetes), underlining the relevance of these findings for RA.…”
Section: Sedentary Behaviour and Rheumatoid Arthritismentioning
confidence: 99%
“…31,32 On the basis of emerging evidence for the association between SB and inflammation, Fenton and Kitas 29 hypothesised that high levels of SB in RA may exacerbate already elevated systemic inflammation in these patients, and contribute to the progression of RA outcomes. Akin to this proposition, Fenton et al 31 summarised results of non-RA studies, demonstrating the adverse links between SB with inflammation and chronic diseases with an inflammatory component (e.g., CVD, type 2 diabetes), underlining the relevance of these findings for RA. That is, as evidence for the associations between SB, inflammation and poor health continues to accumulate, it is important to evaluate the role of SB as an independent risk factor for disease outcomes in RA -a population experiencing compromised health and at high risk of comorbidity.…”
Section: Sedentary Behaviour and Rheumatoid Arthritismentioning
confidence: 99%
See 2 more Smart Citations